Analisis Penambahan Efek Partikel dan Suara yang Indah dan Bervariasi Untuk Meningkatkan Pengalaman Pemain Pada "Game VR Mahakarya” - Adivka, Muhammad Diffgi; Riwinoto, Riwinoto (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2025)
Virtual Reality (VR) technology has brought significant changes to the gaming industry, offering more interactive and immersive experiences. The integration of precise audio-visual elements can further enrich these experiences. While previous studies have examined audio-visual elements in VR games, most have not specifically addressed the impact of particle effects and sound in enhancing player immersion. Therefore, this study incorporates varied particle and sound effects to explore their influence on player immersion in the "Mahakarya VR Game." The research employs a qualitative method, including semi-structured interviews, participatory observation, and thematic analysis to explore players’ subjective experiences. The findings indicate that the addition of varied particle effects, such as crystal glows and visual explosions, along with responsive sound design, can significantly enhance player immersion and overall gameplay satisfaction. This study provides recommendations for VR game developers to more effectively integrate multimedia elements to create more engaging gaming experiences.